Aplikasi Teknologi Bakteri Dalam Pekerjaan Restorasi Sungai Xuxi, Kota Wuxi, China - Yudianto, Doddi; Yuebo, Xie (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2010)
Considering previous successful applications of biological treatment in several restoration works in China, this study is aimed to describe the complete processes and results derived from the application of bacterial technology in restoring urban river. Here the Xuxi River in Wuxi City was selected as an example of case study. Based on the results obtained, it is found that this bacterial technology is able to provide broader views of river restoration work for urban area. Besides it results better water quality, the water is now clearer and contains aquatic life. Although a considerable increase of concentration of total phosphorus, total nitrogen, and ammonium nitrogen may have enhanced to Algae problem during the treatment, but the final results show good achievement. Detail laboratory tests and mathematical model development are necessary to optimize the implementation.Keywords: River restoration, biological treatment, bacterial technology, urban stream, Xuxi River.